ANALISIS MODEL KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL DALAM LINGKUNGAN PENDIDIKAN - Ratna Siti Maulida; Rizqi Nurlaili Muiz; Machdum bachtiar; Eneng muslihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The success of an organization is largely determined by effective leadership. The two most studied and applied leadership approaches in the context of modern management are transformational leadership and transactional leadership. Transformational leadership focuses on efforts to inspire, motivate, and empower organizational members to go beyond personal interests to achieve a common goal. Transformational leaders emphasize long-term vision, positive change, and individual development. Meanwhile, transactional leadership emphasizes the exchange relationship between leader and subordinate, where performance is rewarded through a clear system of rewards and punishments. This research aims to analyze the characteristics, strengths, and shortcomings of each leadership style, as well as its impact on organizational performance. The results of the study show that both leadership styles have complementary roles in various situations, and their effectiveness is greatly influenced by the organizational context, work culture, and characteristics of the individuals involved. A deep understanding of these two styles can assist leaders in choosing the right approach to improve leadership effectiveness and overall organizational success. Keywords: transformational leadership, transactional leadership, organization,